URGENSI PERLUASAN KRIMINALISASI DALAM SISTEM PENDIDIKAN NASIONAL SEBAGAI UPAYA DALAM MEWUJUDKAN FUNGSI SISTEM PENDIDIKAN NASIONAL - Abunawas, Abunawas (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
The national education system as stipulated in Law contains a policy of criminalization of criminal actions based on the scope of the national education system in 5 articles of action, on the development of criminal acts models or forms of criminal acts that occur in the education system has undergone many changes and/or expansion, so it is necessary to expand the criminalization policy to protect the national education system from negative impacts so that it is expected to realize the function of the national education system. With the expansion of the criminalization of acts that can be considered to damage the function of the national education system, it is expected to be able to guarantee the sustainability of the national education system through reformulation of the criminal act model as a last resort (ultimum remedium) of all existing countermeasures (ultima ratio principle) to realize the function of the nation's life.